Canada 2024 - Sainsbury, Brendan; Bujan, Bianca; Heller, Carolyn B.; Donaldson, Cathy; Rhyno, Darcy Keith; Gibb, David; Olsen, Debbie; Bain, Jennifer; Balsam, Joel; Bierman, Jonny; Sinclair, Mandy; Lee, John; et al. (Lonely Planet guidebooks., 2024)
Sighs alternate with gawps at the white-dipped mountains, mist-cloaked seascapes and epic northern roadways. And with more festivals than you can swing a moose at, you ll even forget it 's cold.